Odpowiedzi

2010-04-14T20:11:06+02:00
-(x+7) (x-3) = (-x - 7) (x-3) = -2x + 3x - 7x + 21 = -9x + 24

1 - (z+5) (Z-1) = (- z - 5) (Z - 1) = -zZ +z -5Z +5

4 * x-7/2 - 6 * 3 - x /3
4x - 3,5 - 18 - x/3 (całe działanie pomnożyć przez 3 aby pozbyć się 3 w mianowniku)
4x - 10,5 - 54 - x
12x - 64,5 - x = 11x - 64,5
1 1 1
2010-04-14T20:12:21+02:00
1) -(x+7) (x-3) =-(x2-3x+7x-21)=-x2+3x-7x+21=-x2-4x+21
2) 1- (z+5) (Z - 1) =1-(zZ-z+5Z-5)=1-zZ+z-5Z+5=6-zZ+z-5Z
3) 4 × x-7 (przez 2) - 6 × 3 - x (przez 3)/*6=(3*4*x-7)-(2*6*3-x)=
(12x-7)-(36-x)=12x-7-36+x=13x-43

pozdro liczę na naj :P